ANALISIS PERENCANAAN BAHAN BAKU PAVING BLOCK DENGAN METODE MATERIAL REQUIREMENT PLANNING DI PT. PESONA ARNOS BETON - Atho'illah Fajar Ramadhan; Wiwik Handayani (Jurnal Pendidikan Ekonomi (JURKAMI), 2022)
Supervision and control of raw materials is an important activity to be carried out by industrial players so that there is no excess and shortage of raw material supplies that can hinder the smooth production process. Optimal control of raw materials can minimize inventory costs and the company can determine the right order quantity. This study aims to determine the planning of paving block raw material needs in 2022 in order to minimize costs. The methods used are forecasting, Material Requirement Planning, and Aggregate Planning. The results of the forecasting method show that the Exponential Smoothing method has the smallest standard error. Meanwhile, the MRP results show that the total cost of the LFL method is Rp. 18,565,627 less than the POQ method with a total of Rp. 24,530,943. This shows that the LFL method has a minimum total cost compared to the POQ method. The Aggregate Planning method also shows the production plan per month which is used as the Master Production Schedule. The results of the calculation of Aggregate Planning show a total cost of Rp. 506,752,500. This method allows the company to do Over Time to meet consumer demand even though the company incurs an Over Time fee of Rp. 6,000,000. If the company does not do Over Time, the company will experience a loss because it cannot meet the demand of Rp. 30,195,000